Pengaruh Disiplin dan Motivasi terhadap Kinerja Karyawan pada PLTU Pangkalan Susu Sejahtera - Yushan Radika Devi; Amirudin Amirudin; Mella Yunita (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the effect of Discipline and Motivation on Employee Performance at PLTU Pangkalan Susu Sejahtera. The research was conducted at PLTU Pangkalan Susu Sejahtera with a total of 48 respondents. The sampling technique used in this study was total sampling, so the sample size was 48 respondents. The results of the validity and reliability tests indicate that each question item produced from the questionnaire data is valid and reliable. The data quality tests, namely the normality test, show that the data is normally and significantly distributed. Furthermore, the multicollinearity test also indicates no multicollinearity, as the Tolerance value is >10 and the VIF value is <10. Meanwhile, the heteroscedasticity test shows that the data is not homogeneous, meaning it does not form a specific pattern and is evenly spread throughout the area. The results of the hypothesis test show that, based on the t-test, the variables that influence Employee Performance are Compensation Motivation and Discipline, both of which have an effect. The detailed t-test results are as follows: For variable X1, the t-count is 6.604, while the t-table is 2.014, so t-count (6.604) > t-table (2.014). This is also supported by a significant value of 0.003 (0.003 < 0.050), meaning that Ho is rejected and Ha is accepted, which implies that Discipline has a significant effect on Employee Performance. For variable X2, the t-count is 4.452, while the t-table is 2.014, so t-count (4.452) > t-table (2.014). This is also supported by a significant value of 0.004 (0.004 < 0.05), meaning that Ho is rejected and Ha is accepted, which implies that Motivation has a significant effect on Employee Performance. The F-test result shows that F-count is 11.021, which is greater than the F-table value of 3.20. This is further supported by a significance level of 0.003, which is smaller than α = 0.05, meaning Ho is rejected and Ha is accepted. Discipline and Work Motivation (simultaneously) have an effect on Employee Performance. The R-square value is 62.2%, which means that the independent variables in this study contribute significantly, while the remaining 37.8% is influenced by other factors outside this study.